2001
DOI: 10.1038/86912
|View full text |Cite
|
Sign up to set email alerts
|

The amnionless gene, essential for mouse gastrulation, encodes a visceral-endoderm–specific protein with an extracellular cysteine-rich domain

Abstract: Fate-mapping experiments in the mouse have revealed that the primitive streak can be divided into three functional regions: the proximal region gives rise to germ cells and the extra-embryonic mesoderm of the yolk sac; the distal region generates cardiac mesoderm and node-derived axial mesendoderm; and the middle streak region produces the paraxial, intermediate and lateral plate mesoderm of the trunk. To gain insight into the mechanisms that mediate the assembly of the primitive streak into these functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 22 publications
3
108
0
Order By: Relevance
“…10,19 It has been hypothesized that these truncated AMN products were produced for maintaining a proper embryonic development in mice. 8,19 The same group reconsidered this hypothesis after reporting IGS cases with mutations in exons 7 and 11 which were inconsistent with the production of truncated proteins. 10 It seems, therefore, that the role of AMN in embryonic human development, if any, is less critical than that in mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,19 It has been hypothesized that these truncated AMN products were produced for maintaining a proper embryonic development in mice. 8,19 The same group reconsidered this hypothesis after reporting IGS cases with mutations in exons 7 and 11 which were inconsistent with the production of truncated proteins. 10 It seems, therefore, that the role of AMN in embryonic human development, if any, is less critical than that in mice.…”
Section: Resultsmentioning
confidence: 99%
“…18 It has been suggested that AMN is a 'moonlighting' protein that fulfils 2 functions, one in embryonic development, proved in mice and the other in Cbl absorption, demonstrated in humans. 8,19 In humans, homozygous mutations affecting exons 1-4 of human AMN lead to selective malabsorption of Cbl and no embryonic effect. As a consequence of these mutations, translation initiation occurs downstream and produces truncated AMN proteins in HEK293 transfected cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained from EBs derived from two independent beclin 1 Ϫ/Ϫ ES cell clones. Staining of EBs with antiserum against amnionless (15) revealed that EBs derived from both wt and null mutant ES cells can form VE, although in beclin 1 Ϫ/Ϫ EB, this cell layer was composed of larger, less well organized cells (Fig. 3 a and b, Right).…”
Section: Resultsmentioning
confidence: 99%